Organization of Internet standards - Gençer, Mehmet; Oba, Beyza; Özel, B. lent; Tunalioglu, V. Sinan (Springer, 2006)
In this study we look at a body of standards documents in RFCs(Request For Comments) of IETF(Internet Engineering Task Force). The cross references between these documents form a network. Approaches from social network analysis are deployed to assess centrality of artifacts in this network and identify cohesive subgroups and levels of cohesion. Our results demonstrate major groups centered around key standard tracks, and application of network metrics reflect different levels of cohesion for these groups. As application of these techniques in such domains is unusual, possible uses in open source projects for strategizing are discussed.
International Conference on Open Software (OSS2006) -- JUN 08-10, 2006 -- Como, ITALY
Keywords: Interorganizational Relationships; Biotechnology; Centrality; Network